An Analysis of Speech Act in the Movie "Turning Red" - Hasyifa Diffani; Adhan Kholis (Journal of linguistics, culture and communication, 2023)
A movie consists of a dialogue between its characters. Both the speaker and the listener use many different kinds of utterances. In communication, we use utterances in action, also known as speech actions. This research aimed to determine the types of speech acts performed by the characters and determine the function of the speech acts performed by the characters in Turning Red's movie. A movie can deliver a message to the audience as one form of communication. It contains a variety of genres, making it an interesting topic to be a research. In this case, understanding speech act theory becomes essential for solving the issue. Speech acts are things that can be accomplished through speech. There are three types of speech acts: locutionary, illocutionary, and perlocutionary. The movie has been chosen since it is a children's genre movie representative of Asian parenting style and leaves the deepest messages to children. The data were taken directly from the movie dialogue, focusing on the speech acts uttered by the characters and the context of the occurrence of the utterance. In collecting the data, the researchers transcribed the data comprehensively, which were analyzed using content analysis on the movie Turning Red. The researchers analyzed some illocutionary acts in the movie conversation. The data was divided into five types: directive, representative, declarative, commissive, and expressive. Teachers can create relevant and engaging learning experiences that build pragmatic competence and improve students' communicative skills by adding actual speech acts from movies into language lessons. It helps to understand how movies can be used as valuable instruments in English language teaching, especially in the development of language acquisition.